An agricultural development model to achieve food security in the government of Lamandau Regency, Central Kalimantan Province - Irwansyah, Muhamad; Supriyono, Bambang; Sujarwoto, Sujarwoto; Mardiyono, Mardiyono (Edelweiss Applied Science and Technology, 2025)
This study aims to formulate a decentralization-based agricultural development model to effectively achieve food security in Lamandau Regency, Central Kalimantan. A qualitative approach employing a case study method was used to explore the dynamics of policies, strategies, and agricultural development management practices at the local level. The findings reveal that while the agricultural sector plays a dominant role in the local economic structure, its implementation continues to face significant challenges, including land-use conversion, lack of integrated planning, low community participation, limited data availability, and weak intersectoral coordination. Although regional autonomy presents opportunities for local policy innovation, the study found that limited institutional capacity and suboptimal budget allocation hinder the effectiveness of agricultural development programs. This research proposes an integrated agricultural development model that emphasizes intersectoral synergy, institutional strengthening, optimization of local resources, and enhanced community participation in the planning and implementation of food security programs. The proposed model is designed to be adaptive to local challenges and climate change, while aligning with principles of sustainability. Theoretically, this study contributes to the discourse on development administration, particularly in the context of decentralization and food governance. Practically, the proposed model serves as a reference for formulating more responsive, inclusive, and evidence-based local policies aimed at achieving sustainable food security.